PENETAPAN KADAR KAFEIN DARI BUBUK KOPI YANG DIPEROLEH DARI KOTA SIDIKALANG SECARA SPEKTROFOTOMETRI UV - Maimunah, Siti; Supartiningsih, Supartiningsih; Chandra, Devina (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Coffee has many health benefits, such as stimulating the central nervous system, with the effect of relieving fatigue, drowsiness, and also in creasing concentration power. How ever, excessiveuse of caffeine can cause heart palpitations, stomachdi sorders, and shaking hands. Caffeine levels in coffee circulating in the market vary, dueto a mixtureofotheringredients. For this reason, the National Standardization Agency (BSN) has set a standard for caffeine content in coffeepowder, whichis 0.455%-2% w/w (SNI 01-3542-2004), so that if there is coffee containing high levels of caffeine, it needs to be decaffeinated. tosuppresstheactivityofcaffeine in thebody. The purpose of this study was to determine the caffeine content of Arabica coffee powder and Robusta coffee. The samples determined were 2 types of arabica coffee powder, namely those obtained from high stems and low stems, and 1 robusta coffee powder. Sampling was carried out purposively, and as says were determined using ultraviolet spectrophotometry after extraction using chloroform. The results showed that the caffeine content of high-stem Arabica coffee powder was 1.675% (16.75mg/g), low-stemmed 0.546% (5.462 mg/g), and 0.818% (8.18mg/g) of Robusta coffeegrounds. In conclusion, the caffeine levels of the three samples determinedmet the requirements of the Indonesian National Standard.